THE POSITIVE IMPACT OF SOCIAL MEDIA ON IMPROVING STUDENTS' CHARACTER: AN ISLAMIC EDUCATIONAL PERSPECTIVE - Siti Tresiagati; Khairuddin Lubis (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study aims to analyze the positive impact of social media on the improvement of students' moral conduct (akhlak) from the perspective of Islamic education. The method used is qualitative with a library research approach. Data were collected from various primary and secondary sources, including books, journals, articles, and related documents. The results show that social media can contribute positively to the improvement of students' moral conduct, such as enhancing honesty, responsibility, empathy, politeness, and awareness of worship, when used wisely and accompanied by guidance from educators and parents. This positive impact is particularly evident through religious content, discussion groups on Islamic values, and the examples set by Muslim figures on social media. In conclusion, social media not only carries risks but also holds great potential as a means of moral development in Islamic education. Recommendations are given to teachers, parents, and school administrators to maximize the use of social media as an instrument for moral education.